1994
DOI: 10.1088/0031-8949/49/2/004
|View full text |Cite
|
Sign up to set email alerts
|

120-keV Kr8+– Li collisions studied by near UV and visible photon spectroscopy

Abstract: A spectroscopic analysis of light emitted in the 200-600 nm wavelength range by Kr7+, Kr6+ and Kr5+ ions following 120-keV Kr8+ – Li collisions is performed. Transitions with Δn = 0, 1 and 2 in Kr VIII from n = 6-11 states produced by single electron capture are identified using either ab initio energy level calculations, potential model calculations or atomic energy level data. The production cross sections for single electron capture into the nl sublevels (n = 8 and 9) are deduced from emission cross section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
8
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
4
8
0
Order By: Relevance
“…The present results lend good qualitative support to the inversions suggested by the work of Jacquet et al [8] but as yet there is insufficient accuracy in the experimental data to make worthwhile any further attempts to reconcile them with theory. ACKNOWLEDGMENTS Thanks are due to Dr. F. A. Parpia and Dr. W. P.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The present results lend good qualitative support to the inversions suggested by the work of Jacquet et al [8] but as yet there is insufficient accuracy in the experimental data to make worthwhile any further attempts to reconcile them with theory. ACKNOWLEDGMENTS Thanks are due to Dr. F. A. Parpia and Dr. W. P.…”
Section: Conclusion and Discussionsupporting
confidence: 83%
“…However, a fine-structure inversion is still predicted. The estimate for the 5f interval is in close agreement (perhaps fortuitously) with the experimental result of Jacquet et al [8].…”
Section: Core-polarization Effects B the Multicon6guration Apprsupporting
confidence: 91%
See 1 more Smart Citation
“…At low energies, the significant population of C 3+ (5s) is a direct consequence of successive contributions of avoided crossings between different molecular states in the same n manifold. This is certainly a manifestation of the role played by the core of the partially stripped projectile ion (see also Harel and Jouin [18] and Jacquet et al [19]). In fact, the relative population of different -substates in the capture to a particular n-manifold is a result of two important competing mechanisms (see Jacquet and Pascale [20]): Stark mixing of near-degenerate n substates and the core-electron effect.…”
mentioning
confidence: 95%
“…This is expected due to the fact that a larger amount of positive charge inside the nucleus of N 5+ makes its core much more compact, albeit they have identical He-like structure. Pascale and co-workers [19,20] have also found via various experimental and classical trajectory Monte Carlo (CTMC) studies that the enlarged size of the projectile core tends to have an enhanced population of states with small angular momenta. Rieger et al [21], in their CTMC calculation have shown that the population of the ns state is significantly larger for the N 5+ projectile as compared to B 5+ on the same Li target.…”
mentioning
confidence: 99%